THE EFFECT OF GIVING PINEAPLE PEEL EXTRACT (Ananas comosus L. Merr) THROUGH DRINKING WATER TO DIGESTIVE SYSTEM OF MALE BALI DUCK - E.O.D., Saragih,; Puspani, E.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
Ducks are one of the poultry that are in demand by the community to meet protein needs. Duck growth is related to the health of the digestive system, because the health of the livestock's body is also determined by the condition of the digestive system. To maintain the health of the duck's digestive system, pineapple peel extract can be used. This study aims to determine the effect of giving pineapple peel extract through drinking water on the digestive system of male bali ducks. The design used was a completely randomized design (CRD) consisting of four treatments and four replications. Each replication contained three male bali ducks, so that the total number of male bali ducks used was 48. The treatments given were giving drinking water without pineapple peel extract as a control (P0), giving 6% pineapple peel extract through drinking water (P1), giving 8% pineapple peel extract through drinking water (P2), giving 10% pineapple peel extract through drinking water (P3). The variables observed were the percentage of proventriculus, ventriculus, pancreas, bile, liver, small intestine and length of small intestine. The results showed that the administration of pineapple peel extract through drinking water had no significant effect (P>0.05) on the percentage of proventriculus, ventriculus, pancreas, gallbladder, liver, small intestine and length of small intestine. Based on the results of the study, it can be concluded that the administration of pineapple peel extract through drinking water at a level of 6-10% does not affect the digestive system of male bali ducks.